UPAYA PENINGKATAN AKTIVITAS DAN HASIL BELAJAR EKONOMI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH SISWA KELAS X SMA IT SMART INSANI - Arni, Yusni (LPPM STKIP PGRI Bandar Lampung, 2016)
The improving activity and result economic studies learning through cooperative model make a match type in X grade student of Senior High school IT Smart Insani. The purpose of this research was to improve the economic learning through cooperative model make a match type in X grade SMA IT Smart Insani. This research uses classroom action research techniques. The research was conducted in three cycles. Subject of this study is the X grade student of Senior Highh school IT Smart Insani. Which has 20 students. Data sources come from teachers, students and researchers. Data collection techniques using observation, testing, interview and documentations.The validity of data using triangulation methods techniques and other sources. Analysis of the data used by the qualitative and quantitative analysis. The result showed that the use of cooperative learning Make a match type can improve the economic studies learning.